Endumeni and Water Trading in the Superior Courts: Falling Short of a Unitary Approach to Statutory Interpretation - Tracy-Lynn Field (Potchefstroom Electronic Law Journal, 2025)
This article critiques recent decisions on water trading in the superior courts in light of the approach to statutory interpretation set out in Natal Joint Municipal Pension Fund v Endumeni Municipality (2012 (4) SA 593 (SCA)). The Endumeni approach, which is the preferred modern approach to statutory interpretation, entails a unitary interpretive technique whereby text and context are interpreted together from the outset. Following CSARS v United Manganese of Kalahari (Pty) Ltd (2020 (4) SA 428 (SCA), context extends beyond the statutory enactment to constitutional, historical and purposive considerations. The article presents an updated account of the Endumeni approach and analyses five water trading decisions through this lens. It finds that the water trading decisions fall short of a unitary approach as a result of their failure to anchor their analysis in the correct parts of section 25 of the National Water Act 36 of 1998, over-reliance on the statutory context, limited consideration of constitutional, historical and purposive contexts, and reliance on arguments indirectly invoking the intention of the legislature.